The Effect of Using VIRASAT Media (Virtual Reality–Based Sexual Education) on Adolescent Behaviors Leading Toward Free Sex - Yosef Marsianus Karno; Nastain Abubakar Pattimura; Yudiarsi Eppang; Maryone Saija; Melawati Wakano (Indonesian Journal of Global Health Research, 2026)
Currently, it is estimated that there are 39.9 million people living with HIV worldwide. In the Asia-Pacific region, there are approximately 6.7 million people living with HIV. In Indonesia, it is estimated that there are around 564,000 people living with HIV. Data from the National Commission for Child Protection shows that 93.7% of adolescents in Indonesia have engaged in kissing, petting, and oral sex. Adolescents' knowledge regarding sexuality is still relatively low. Sexual education is a way to reduce the spread of sexually transmitted diseases. This study aims to determine the influence of VIRASAT (Virtual Reality Sexual Education) media on adolescent behavior leading to free sex. This study used a pre-experimental one-group pretest–posttest design involving 80 students from SMAN 14 Ambon selected through stratified random sampling. Data on knowledge, attitudes, and behaviors related to free sex were collected using a structured questionnaire administered before and after a virtual reality–based sexual education (VIRASAT) intervention under researcher supervision. The effect of the intervention was analyzed using a paired t-test. The results showed that after the intervention, the majority of respondents had high knowledge (63.8%) with a p-value of 0.013. After the intervention, the majority of respondents had a positive attitude (67.5%) with a p-value of 0.005. After the intervention, the majority of respondents exhibited non-risky behavior (68.8%) with a p-value of 0.004. Thus, it can be interpreted that there is a significant influence between the use of VIRASAT (virtual reality sexual education) media on adolescent behavior leading to free sex at SMAN 14 Ambon. The use of VIRASAT (Virtual Reality Sexual Education) media had a significant effect on adolescents’ knowledge, attitudes, and behaviors related to free sex at SMAN 14 Ambon. After the intervention, most respondents demonstrated high knowledge, positive attitudes, and non-risky sexual behaviors, indicating that VIRASAT is an effective educational medium for preventing risky sexual behavior among adolescents.